Pengaruh Sistem Jaminan Kesehatan Nasional (Jkn) Terhadap Pelayanan Konservasi Gigi Di Fktp Kota Surakarta - Widyastuti, Noor Hafida; Narulita, Danti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Background of this study was National Health Insurance started on 1st January 2014. Dentist in Primary Health Care as a provider in primary case, these are promotive, preventive, curative and rehabilitative. This principle as a focus service in national Health Insurance System as gatekeeper. These concepts are credentialing and re-credentialing, four function of primary care these are first contact, continuity, comprehensive, coordination, competit ion and quality and cost control. Aim of this study to determine the impact of National Health Insurance system toward conservative dentistry treatment in Primary Health Care in Surakarta. Methods of this study was observational analytic with cross sectional study. The research subject were dentist who work in Primary Health Care in Surakarta. This research performed at Primary Health Care at Surakarta on February 2019. Instrument of this study were questionnare of National Health Insurance system and conservative dentistry treatment. Result of this study was majority of respondent (92%) have an optimal categorical applying National Health Insurance system and respondent (42%) have a good categorical giving a conservative dentistry treatment. Based on statistical test that has been done there is significant impact on both variables with p<0,05. Conclusion was there is an impact beetween National Health Insurance system and conservative dentistry treatment in Primary Health Care in Surakarta